Treasury of Christmas stories - McGovern, Ann; Lockhart, David (New York : Galahad Books, 1974)
Thirty Christmas stories and poems by well-known authors, including Edgar Allan Poe, William Dean Howells, Hans Christian Andersen, Clement Moore, and Laura Ingalls Wilder.
Keywords: Christmas stories; Christmas -- Juvenile poetry; Christmas stories; Christmas poetry